2020
DOI: 10.1111/jcmm.15806
|View full text |Cite
|
Sign up to set email alerts
|

The long non‐coding RNA SNHG1 promotes bladder cancer progression by interacting with miR‐143‐3p and EZH2

Abstract: Bladder cancer (BC), one of the most lethal neoplasms of the genitourinary system worldwide, has shown a trend towards increasing incidence and mortality rates in recent years. 1 Despite substantial progress in understanding the pathophysiology of BC, the exact mechanisms underlying bladder carcinogenesis remain unclear. Therefore, identifying novel molecular targets and more effective therapeutic approaches is of crucial importance to improve the treatment and prognosis of BC. Currently, emerging evidence has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…An increasing number of studies have demonstrated the essential role of lncRNAs in bladder cancer development, such as lncRNA SNHG1, lncRNA DLX6-AS1, and lncRNA SNHG3. All these lncRNAs facilitate bladder cancer progression by enhancing cell growth and reducing cell apoptosis [ 47 49 ]. Furthermore, several studies have revealed that LINC00958 acts as an oncogenic driver in bladder cancer [ 14 , 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the essential role of lncRNAs in bladder cancer development, such as lncRNA SNHG1, lncRNA DLX6-AS1, and lncRNA SNHG3. All these lncRNAs facilitate bladder cancer progression by enhancing cell growth and reducing cell apoptosis [ 47 49 ]. Furthermore, several studies have revealed that LINC00958 acts as an oncogenic driver in bladder cancer [ 14 , 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that noncoding RNAs (ncRNAs) play important roles in multiple diseases ( Kurt et al., 2020 ; Mi et al., 2020 ; Xiang et al., 2020 ). Among these ncRNAs, long noncoding RNAs (lncRNAs) are more than 200 nucleotides in length and have limited or no protein-coding capacity ( Liu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et al proved that lncRNA GASL1 inhibited cell proliferation and metastasis by sponging microRNA-106a in gastric carcinoma [ 39 ]. Xiang et al confirmed that SNHG7, as an endogenous ceRNA, could regulate HK2 expression via sponging miR-143-3p to promote the proliferation of bladder cancer [ 40 ]. Besides, in hepatocellular carcinoma, lncRNA NKILA has been reported for suppressing NF-κB/Slug pathway mediated with epithelial-mesenchymal transition to inhibit tumor metastasis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%